2023
DOI: 10.1186/s40945-023-00163-8
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in the management of patients with low back and neck pain: a retrospective analysis of 82 people treated solely in the metaverse

Abstract: Background Clinically, neck pain disorders (NPD) and non-specific low back pain (NS-LBP) are respectively the fourth and first most common conditions associated with the greatest number of years lived with disability. Remote delivery of care may benefit healthcare sustainability, reduce environmental pollution, and free up space for those requiring care non-virtual care. Methods A retrospective analysis was performed on 82 participants with NS-LBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Participants did not report any deterioration in their condition during the course of treatment using VR in the Metaverse. This favorable result emphasizes the safety and potential of VR as a safe approach to managing patients with low back and neck pain, further reinforcing its value as a therapeutic tool in the field of physical rehabilitation (33).…”
Section: Metaverse Equitable Rehabilitation Therapy (Merth) Frameworkmentioning
confidence: 67%
See 2 more Smart Citations
“…Participants did not report any deterioration in their condition during the course of treatment using VR in the Metaverse. This favorable result emphasizes the safety and potential of VR as a safe approach to managing patients with low back and neck pain, further reinforcing its value as a therapeutic tool in the field of physical rehabilitation (33).…”
Section: Metaverse Equitable Rehabilitation Therapy (Merth) Frameworkmentioning
confidence: 67%
“…Moreover, disability decreasing from non-specific low back pain significantly decreased by 17.8% (p < 0.001) as measured by the Modified Oswestry Low Back Pain Disability Index, and Neck Disability Index improved by 23.2% (p = 0.02). These findings highlight the potential benefits of incorporating VR in pain management and rehabilitation, offering a comprehensive approach to address various aspects of patients' pain (33). Additionally, the study demonstrated promising outcomes concerning adverse events.…”
Section: Metaverse Equitable Rehabilitation Therapy (Merth) Frameworkmentioning
confidence: 68%
See 1 more Smart Citation
“…A metaverse-based virtual reality therapy program appeared to be safe, according to research by Orr et al (2023). Researchers gathered the information for more than 40 outcome metrics.…”
Section: Metaverse In the Healthcare Domainmentioning
confidence: 99%
“…Orr et al [32] wanted to assess the feasibility, safety, and suitability of exercise therapy utilising virtual reality (VR) in addressing neck pain disorders (NPD) and non-specific low back pain (NS-LBP), along with identifying appropriate outcome measures. Participants were equipped with the Pico Neo 2 (ByteDance) head-mounted display (HMD) and hand controllers.…”
Section: Neck Painmentioning
confidence: 99%